Hypopigmented Macules as Manifestation of Lichen Planus and Lichen Planopilaris. (July 2019) - Arnold, David; Hoffman, Melissa B.; Onajin, Oluwakemi; Sangüeza, Omar P.; McMichael, Amy
Abstract : Abstract: Lichen planus (LP) is an idiopathic inflammatory disease of the skin, hair, nails, and mucous membranes. Classic cutaneous LP is characterized by violaceous flat-topped papules that typically favor the extremities. LP on the scalp, otherwise known as lichen planopilaris, classically presents with scarring alopecia, perifollicular erythema and follicular prominence. Although LP pigmentosus presents primarily as hyperpigmentation, there is only one previous report of hypopigmented LP. In this report, the authors report 2 cases of LP that presented primarily as hypopigmented macules in 2 African American men. The first patient presented with hypopigmented macules on face and scalp as well as trunk and extremities. The second patient presented with hypopigmented macules on scalp with associated alopecia. Histopathological examination from both patients showed features of LP. The authors propose a new variant of LP that presents acutely as hypopigmented lesions.